Driving Style, Psychological Well-being, and Road Safety Behavior of Drivers: A Critical Review - Singh, Garima; Dubey, Anubhuti (Utan Kayu Publishing, 2025)
Understanding the relationship between psychological well-being and driving style is essential for addressing public health issues related to road safety. Road accidents impose substantial economic, social, and emotional burdens. This review aims to (1) identify psychological and behavioral determinants of driving behavior, (2) explore how driving style moderates the link between psychological well-being and road safety behavior, and (3) evaluate interventions that promote safer driving outcomes. A systematic review of 30 empirical studies (20 international, 10 Indian) published between 2000 and 2025 was conducted using databases such as PubMed, Scopus, Google Scholar, ScienceDirect, and ResearchGate. Studies were selected based on relevance, empirical rigor, and focus on psychological factors in driving. The review was framed using the Theory of Planned Behavior and the Stress-Strain Model. Findings reveal that psychological distress (e.g., stress, fatigue) contributes to aggressive and risky driving, while higher well-being correlates with defensive, safer driving styles and improved risk perception. Defensive driving mitigates the adverse impact of poor mental health on behavior. Promising interventions include stress management training, psychological education, and real-time driver feedback systems. Future research should focus on culturally adapted, evidence-based interventions targeting high-risk groups, supporting integration of psychological screening and mental health strategies into driver education and road safety policy.